Obesity As Based on Body Mass Index Unrelated to Blood Pressure in Women of Childbearing Age, Age 20–29 Years - Lubis, Irfan Darfika; Habib, Muhammad Zhafron (Buletin Farmatera, 2026)
Abstract: Obesity is one of the main risk factors for hypertension. Women of childbearing age are prone to obesity due to an unbalanced diet, low physical activity, and hormonal influences. This study aims to determine the relationship between obesity and blood pressure in women of childbearing age (20–29 years). This study is an analytical descriptive study with a cross-sectional design involving 72 obese women of childbearing age in Medan Deli District, Medan City, North Sumatra Province. Samples were taken purposively, with direct measurements of body weight, height, and blood pressure. BMI is categorised as obesity level I (58.3%) and II (41.7%). The majority of blood pressure was hypertension of the first degree (54.2%), normal (25.0%), and pre-hypertension (20.8%). The Fisher test showed no significant association between obesity and blood pressure (p = 0.634). There was no significant association between obesity and blood pressure in women of childbearing age aged 20–29 years. Young age and the possible protective effects of the hormone estrogen, which increases vasodilation through nitric oxide and lowers oxidative stress, are thought to play a role in preventing an increase in blood pressure despite obesity.